Pelaksanaan Pembayaran Iuran PAM - Harahap, Hamdan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Water is the source of life for living things, especially humans, with water humans can carry out daily activities to the fullest. All community members consume clean water from wells, rivers and PAM Water. It is the same with residents in Batu Sundung Village, located in Padang Lawas Regency, North Sumatra, where most of the residents consume PAM Water for their daily lives. In addition to the great benefits, there are several problems from the residents regarding the Water PAM used, namely the problem of payment fees that are too large, not in accordance with the water they get. So from this problem the author is interested in researching the payment of Air PAM fees in Batu Sundung Village in terms of KHES. The theoretical study used by the author in analyzing this is KHS (Compilation of Sharia Economic Law), concerning Amwal and Akad. The research methodology uses field research (field research), and data collection techniques used by observation and interviews. The results found were that problems related to PAM Water payment fees occurred in 2018 at the beginning of the establishment of PAM Water, the community did not know about the problem of fees that must be paid, and after 2019 the Village Head, PAM SIMAS Chair, and Village residents had held a deliberations and decided that the payment PAM fees are according to the meter, and per meter must pay Rp. 2,000. and from this decision the residents began to feel clear how much water they had to spend per day to be paid monthly after the QS. An-nisa paragraph 29, continued that the provider of wages/salaries to officers who maintain water supply comes from cash contributions of Rp. 5,000 / month, this is in accordance with the hadith of the apostle about the provision of wages / salaries that are in accordance with the work. And all that is offered by Sharia Economic Law aims to be mutually beneficial, not only for personality.